Methodology for determining permissible operating modes of DC traction motor of quarry dump truck to ensure satisfactory commutation - V. V. Kharlamov; Yu. V. Moskalev; S. N. Naiden (Омский научный вестник)
The article considers an approach to determining the permissible ranges of changes in the armature voltage, armature current and the excitation coefficient of the DC traction motor of a mining dump truck to ensure satisfactory commutation. When the DC motor is running in the specified modes, the probability of sparking in the collector-brush unit with a degree of 2 points will be minimal. A method for determining the permissible operating modes of a mining dump truck traction motor to ensure satisfactory commutation is proposed. The method allows, based on the analysis of experimental data, to determine the permissible ranges of changes in voltage, armature current and excitation coefficient, at which the degree of sparking does not exceed 1½ points.